Functional significance of voltage-dependent conductances in Limulus ventral photoreceptors (The Rockefeller University Press, 1982)
The influence of voltage-dependent conductances on the receptor potential of Limulus ventral photoreceptors was investigated. During prolonged, bright illumination, the receptor potential consists of an initial transient phase followed by a smaller plateau phase. Generally, a spike appears on the rising edge of the transient phase, and often a dip occurs between the transient and plateau. Block of the rapidly inactivating outward current, iA, by 4-aminopyridine eliminates the dip under some conditions. Block of maintained outward current by internal tetraethylammonium increases the height of the plateau phase, but does not eliminate the dip. Block of the voltage-dependent Na+ and Ca2+ current by external Ni2+ eliminates the spike. The voltage-dependent Ca2+ conductance also influences the sensitivity of the photoreceptor to light as indicated by the following evidence: depolarizing voltage- clamp pulses reduce sensitivity to light. This reduction is blocked by removal of external Ca2+ or by block of inward Ca2+ current with Ni2+. The reduction of sensitivity depends on the amplitude of the pulse, reaching a maximum at or approximately +15 mV. The voltage dependence is consistent with the hypothesis that the desensitization results from passive Ca2+ entry through a voltage-dependent conductance.